2021
DOI: 10.3389/ijph.2021.1604220
|View full text |Cite
|
Sign up to set email alerts
|

Gender Inequality and Mental Health During the COVID-19 Pandemic

Abstract: Objective: We explore gender differences in mental health deterioration and psychological well-being due to the COVID-19 pandemic, as well as the mechanisms through which these differences may operate.Methods: Using data from the Life during Pandemic survey in Chile, which covers 2,545 adult respondents, we estimate econometric models to explore gender differences in psychological well-being and mental health as well as economic fragility and household workload during the COVID-19 pandemic.Results: We find wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 20 publications
2
32
0
6
Order By: Relevance
“…Many of these countries are characterized by high levels of economic and health inequality, fragile health systems, and high levels of informality and economic fragility [ 44 ]. In particular, these features where exacerbated in Chile since the onset of the COVID-19 pandemic, as transmission and mortality rates were found to be related to socioeconomic characteristics [ 45 ], there is gender inequality in mental health deterioration and psychological well-being [ 46 ], psychological distress is linked to measures of economic uncertainty [ 47 ], and increases in food insecurity [ 48 ] and domestic violence [ 49 ] were reported. In our study we dive deeper into economic vulnerability and several financial problems arising from different household expenditures and household debt, which were previously unexplored in this context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these countries are characterized by high levels of economic and health inequality, fragile health systems, and high levels of informality and economic fragility [ 44 ]. In particular, these features where exacerbated in Chile since the onset of the COVID-19 pandemic, as transmission and mortality rates were found to be related to socioeconomic characteristics [ 45 ], there is gender inequality in mental health deterioration and psychological well-being [ 46 ], psychological distress is linked to measures of economic uncertainty [ 47 ], and increases in food insecurity [ 48 ] and domestic violence [ 49 ] were reported. In our study we dive deeper into economic vulnerability and several financial problems arising from different household expenditures and household debt, which were previously unexplored in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Our sample covers a higher proportion of professionals and men, and therefore results cannot be extrapolated to the entire population. However, we expect the segments of the population analyzed to be less financially constrained [ 46 ]; if this is the case our estimates should be biased towards zero, and are therefore conservative estimates of the overall relationship between financial fragility and mental health. At the time of our study no nationally-representative surveys from the government or other institutions allowed to explore the link between financial fragility and mental health during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID 19 pandemic is an event with a great impact on the entire population worldwide; Various sectors of the economic, political and social world have been affected as a direct consequence of the situation. From the health sector, it is essential to report on the emerging phenomena during the global emergency, as well as the dynamics that are being created around, in this case, mental health [8,9]. COVID-19 has affected specific population groups in one way or another; health workers, children, young people, older adults and people with pre-existing health conditions, people in humanitarian settings and situations of conflict, where the problems studied were loneliness, nervousness, agitation, irritability and difficulty concentrating.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that there are sex differences in the neurobiological mechanisms involved in stress, anxiety and affective disorders, where females have an increased risk of presenting these symptoms ( 71 , 72 ). Furthermore, a study in the general population in Chile found that females were more likely to have a new mental health disorder during the pandemic than males ( 73 ).…”
Section: Discussionmentioning
confidence: 99%